2017
DOI: 10.1371/journal.pone.0180532
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular biosynthetic parameters and metabolic profile in different life stages of Leishmania braziliensis: Amastigotes as a functionally less active stage

Abstract: It was recently hypothesized that Leishmania amastigotes could constitute a semi-quiescent stage characterized by low replication and reduced metabolic activity. This concept developed with Leishmania (Leishmania) mexicana and Leishmania (Leishmania) major models might explain numerous clinical and sub-clinical features of Leishmania (Viannia) braziliensis infections, like reactivation of the disease, non-response to chemotherapy or asymptomatic infections. We compared here in vitro the proliferative capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 59 publications
8
28
0
2
Order By: Relevance
“…In L. infantum Ama Axe showed a decreased rate of synthesis of proteins and amount of polyribosomes (30). Similarly, our previous study in L. braziliensis showed that Ama Axe downregulate their levels of rRNA to 15 % of the levels found in Pro Log (13). In present study, we showed that Ama Axe of both L. mexicana and L. braziliensis had an overall downregulated rGFP expression equivalent to 10% of the levels found in Pro Log .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In L. infantum Ama Axe showed a decreased rate of synthesis of proteins and amount of polyribosomes (30). Similarly, our previous study in L. braziliensis showed that Ama Axe downregulate their levels of rRNA to 15 % of the levels found in Pro Log (13). In present study, we showed that Ama Axe of both L. mexicana and L. braziliensis had an overall downregulated rGFP expression equivalent to 10% of the levels found in Pro Log .…”
Section: Discussionsupporting
confidence: 75%
“…Analyzing the whole population of cells, they found several quiescence traits among amastigotes: a substantially increased generation time in comparison to promastigotes (12 days vs 9 hours, respectively), plus lower synthesis of RNA, proteins, lipids (12). Our group achieved the same conclusion for another species, L. braziliensis and we described a drop in the levels of macromolecules involved in the ribosome biogenesis (ribosomal RNA and proteins (13), a signature of quiescence encountered from prokaryotes as Mycobacterium to eukaryotes as Sacharomyces (1416). Quiescence complexity was further addressed by a third study that explored the homogeneity of quiescence among L. major amastigotes in vivo (17) .…”
Section: Introductionsupporting
confidence: 65%
“…To our knowledge, this is the first report of extended dormancy in an otherwise replicating stage of any trypanosomatid. In the related protozoan Leishmania sp, intracellular amastigotes exhibit greatly reduced proliferation and metabolism relative to the extracellular promastigote forms ( Jara et al, 2017 ) and have been described as ‘semi-quiescent’ but steadily replicating in vivo with a doubling time of 12 days for L. mexicana ( Kloehn et al, 2015 ). Studies in L. major by Mandell and Beverley documented slow growing (~60 hr doubling time) and even slower dividing, BrdU-non-incorporating intracellular amastigotes in mouse infections but the technical limitations of the labeling procedure prevented a definitive conclusion of dormancy ( Mandell and Beverley, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the in vivo susceptibility could still vary based on the metabolic state of the L. major or L. mexicana parasites in the skin. In chronic lesions with slow disease onset, a quiescent semidormant phenotype of L. mexicana could exist, benefitting its long-term survival and possibly showing reduced drug sensitivity ( 53 55 ). Such PK/PD factors could cause variable rate or magnitude of parasite elimination, a combined outcome of drug activity and host immunity.…”
Section: Discussionmentioning
confidence: 99%